2'- (5-bromo-1H-indol-3-yl)methylene -2-(1H-indol-3-yl)acetohydrazide ethyl acetate solvate - Ali, Hapipah Mohd; Ng, S.W.; Shimar, J.N. (International Union of Crystallography, 2007)
The constituent molecules of the title compound, C19H15BrN4O·C4H8O2, are linked by hydrogen bonds into a linear chain, with the acetohydrazide O atom serving as acceptor to the amide group as well as to the amino group of the bromoindole group. The ethyl acetate solvent molecule is also hydrogen bonded to the chain.